(untitled) (Research, Society and Development, 2022)
The objective of this article is to propose the creation of an atmospheric condition index using Artificial Intelligence tools. The atmospheric condition can be obtained from parameters that the scientific communities – environment, health, labor safety – adopt for the different pollutants in the atmosphere. Parameters were obtained from the scientific literature and specialists, who were consulted about the objective data to allow an analysis through an expert system. As the data are from highly imprecise sources, classic-logic (binary) systems do not fit. We opted to use the Evidential Annotated Paraconsistent Logic. This non-classical logic naturally accommodates imprecisions, contradictions, and paracompleteness without the danger of trivialization. Thus, the Evidential Annotated Paraconsistent Logic can be ideally adopted as a valuable tool for controlling atmospheric conditions, especially in large metropolises.